THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHING RECOUNT TEXT TO THE TENTH GRADE STUDENTS OF VOCATIONAL SCHOOL - Susi Suryati; Hazairin Eko Prasetyo (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to describe how the implementation of scientific approach influences the score of the students and to describe the techniques or procedures the teacher used in teaching recount texts through scientific approach to improve the tenth grade students’ writing. This research used quantitative research and focused on the regression of the teacher that implements the scientific approach and the teacher to improve the students’ writing competence in recount texts which were taken from class X accounting 1 of SMKN 1. First, the regression of the variable X toward variable Y was low because R Square of the teacher was 0.306 and R Square of the writer was 0.356. Second, the teacher improves the students with the second time remedial test and Belajar Ulang in the next semester. In brief, not only the approach but also the other factors influence the learning process in addition to the teacher who has paid attention to other factors to get a maximum result of the students’ activities.